Foldability of a Natural De Novo Evolved Protein - Bungard, Dixie; Copple, Jacob S.; Yan, Jing; Chhun, Jimmy J.; Kumirov, Vlad K.; Foy, Scott G.; Masel, Joanna; Wysocki, Vicki H.; Cordes, Matthew H.J. (Quarterly Journal of Economics, 2017)
The de novo evolution of protein-coding genes from noncoding DNA is emerging as a source of molecular innovation in biology. Studies of random sequence libraries, however, suggest that young de novo proteins will not fold into compact, specific structures typical of native globular proteins. Here we show that Bsc4, a functional, natural de novo protein encoded by a gene that evolved recently from noncoding DNA in the yeast S. cerevisiae, folds to a partially specific three-dimensional structure. Bsc4 forms soluble, compact oligomers with high β sheet content and a hydrophobic core, and undergoes cooperative, reversible denaturation. Bsc4 lacks a specific quaternary state, however, existing instead as a continuous distribution of oligomer sizes, and binds dyes indicative of amyloid oligomers or molten globules. The combination of native-like and non-native-like properties suggests a rudimentary fold that could potentially act as a functional intermediate in the emergence of new folded proteins de novo.